Judith - Koosed, Jennifer L. (Wisdom Commentary Ser., 2022)
Judith -- Acknowledgments -- Abbreviations -- Contributors -- Foreword: "Tell It on the Mountain"-or, "And You Shall Tell Your Daughter [as Well]" -- Editor's Introduction to Wisdom Commentary: "She Is a Breath of the Power of God" (Wis 7:25) -- Authors' Introduction -- Judith 1:1-4:15: The Masculine Machinations of War -- Judith 5:1-6:21: Achior, a Different Kind of Man -- Judith 7:1-9:14: Judith Takes Center Stage -- Judith 10:1-11:23: High Femme Warrior -- Judith 12:1-13:10a: Wielding the Master's Tool -- Judith 13:10b-16:25: Judith Triumphant -- Conclusion -- Works Cited -- Index of Scripture References and Other Ancient Writings -- Index of Authors and Subjects.